Momentum effect all over the world - Imran, Zulfiqar Ali; Wong, Woei Chyuan; Ismail, Rusmawati (Universiti Utara Malaysia, 2017)
This study is intended to reaffirm the existence and profitability of momentum investment strategies in 40 countries around the world during the period 1996–2018.The contradictory findings of previous research on the existence and profitability of momentum strategies have raised a pertinent question on the validity of efficient market hypothesis. We documented the momentum effect in 90% of our sample countries of which 52.5% exhibited positive momentum effect while 37.5% exhibited negative momentum effect. The findings were robust to two distinct sub-period analyses. The clear rejection of efficient market hypotheses is valuable to momentum traders and stock market regulators.The International Journal of Banking and Finance, Vol. 13. Number 2, 2017: 75-93751. IntroductionFinance literature carries substantial evidence on the existence and profitability of momentum returns since the seminal work of Jegadeesh and Titman (1993). Many studies have documented instances where stocks kept on outperforming (underperforming) for the next three to 12 months if they had outperformed (underperformed) during several previous months. Jegadeesh and Titman (1993)